The effects of vitamin C and menthone on acyclovir induced DNA damage in rat spermatozoa: An experimental study - Shima Toghiani; Nasim Hayati Roudbari; Gholam Reza Dashti; Shahla Rouzbehani (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Acyclovir (ACV) is known to be toxic to gonads, inducing apoptosis in the reproductive system. The beneficial effects of vitamin C (Vit C) and menthone, both as antioxidant agents on various organs has been reported. Objective: This study evaluated the potential role of the Vit C and menthone on the DNA damage in rat spermatozoa induced by the ACV. Materials and Methods: In this experimental study, adult male albino Wistar rats with average weight of 250±10 gr, were divided into six groups (n=18/each), as: ACV (15 mg/kg/day), ACV+Vit C (20 mg/kg/day), ACV+ menthone (100 µl/d), ACV+ menthone (250 µl/d), ACV+ menthone (400 µl/day) and control group without any treatment. At the end of experiment, the animals were sacrificed and sperm samples were collected and isolated in phosphate-buffered saline and examined by TUNEL staining process. The percentage of TUNEL positive spermatozoa was evaluated by fluorescence microscopy. Each experiment was performed in three repeats. Results: Male rats exposed to ACV had significant increase in DNA damages in comparison to other groups. The percentage of TUNEL positive sperm cells was 90.83 (p<0.001) in ACV group. The protective role of both antioxidants used in high dose, compensate the adverse effects of the ACV. The results showed that the percentage of apoptotic sperm in the ACV+Vit C group was 16.38 (p<0.001) and in the ACV+ menthone (400 µl/d) group was 16.05 (p<0.001). Conclusion: The present results showed that Vit C and menthone at higher dose have a good compensatory effect with significant reduction in DNA damages in sperm cells by reversing the adverse effect of ACV on the reproductive system in male rat.